T-cell/Natural killer-cell neoplasms presenting as leukemia- Case series from single tertiary care center - Naseem, Shano (Int J Hematol Oncol Stem Cell Res, 2016)
Background: Mature T/ NK-cell neoplasms are a rare group of disorders and their presentation as leukemia is even rarer. Most of the previous studies have focused on mature B-cell lineage leukemias and there is a paucity of data on mature T/NK-cell lineage leukemias. We, therefore, planned this study to analyze their spectrum, frequency, morphology and immunophenotypic features. Subjects and Methods: All cases of lymphomas presenting as leukemia over a period of two and a half years were evaluated. Detailed analysis of cases with T/NK-cell lineage was done for their clinical, hematological and immunophenotypic features. Results: A total of 262 cases of mature lymphoid neoplasms presented as leukemia during the study period. Of whom, only 8 (3.1%) cases were of T /NK-cell lineage and the remaining (96.9%) were of B-cell lineage. Of 8 cases, 4 (50%) had T-prolymphocytic leukemia, 2 (25%) had chronic lymphoproliferative disorder- natural killer cell and 1 (12.5%) case of each T-large granular lymphocytic leukemia and hepatosplenic γ/δ T-NHL. Conclusion: T/NK-cell leukemias are rare. Along with clinical and morphological features, pattern of immunophenotypic markers is vital for their diagnosis and subcategorization.